2010
DOI: 10.1371/journal.pone.0009625
|View full text |Cite
|
Sign up to set email alerts
|

Unique Biological Properties of Catalytic Domain Directed Human Anti-CAIX Antibodies Discovered through Phage-Display Technology

Abstract: Carbonic anhydrase IX (CAIX, gene G250/MN-encoded transmembrane protein) is highly expressed in various human epithelial tumors such as renal clear cell carcinoma (RCC), but absent from the corresponding normal tissues. Besides the CA signal transduction activity, CAIX may serve as a biomarker in early stages of oncogenesis and also as a reliable marker of hypoxia, which is associated with tumor resistance to chemotherapy and radiotherapy. Although results from preclinical and clinical studies have shown CAIX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 44 publications
1
48
2
3
Order By: Relevance
“…To ascertain the ability of these antibodies to mediate immune cell killing of CAIX-expressing RCC cells, we chose to analyze high affinity scFv-Fc antibodies that either inhibited the CA activity of CAIX, but did not internalize (G37 and G39), or showed minimal to modest inhibition of CA activity and induced internalization of CAIX (G10, G36, and G119) [23]. We utilized RCC cell lines with high CAIX (SKRC-09, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain the ability of these antibodies to mediate immune cell killing of CAIX-expressing RCC cells, we chose to analyze high affinity scFv-Fc antibodies that either inhibited the CA activity of CAIX, but did not internalize (G37 and G39), or showed minimal to modest inhibition of CA activity and induced internalization of CAIX (G10, G36, and G119) [23]. We utilized RCC cell lines with high CAIX (SKRC-09, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various antibodies targeting the tumor-associated antigen CAIX on RCC cells have been amongst those most extensively studied [8, 21, 23, 24, 34], owing to the antigen’s high expression on RCC. One chimeric anti-CAIX antibody that does not inhibit enzymatic activity, girentuximab, has been evaluated in the clinic [24, 43].…”
Section: Discussionmentioning
confidence: 99%
“…These dramatic effects illustrate the importance of extracellular CA activity and may explain the correlation between CAIX/CAXII expression in tumour tissue samples and poor patient prognosis (Saarnio et al, 1998;Liao and Stanbridge, 2000;Chia et al, 2001;Koukourakis et al, 2001;Loncaster et al, 2001;Potter and Harris, 2003;Haapasalo et al, 2006;Haapasalo et al, 2008). These results make a case for clinical trials for studying the responsiveness of tumours in patients to anti-CAIX/anti-CAXII therapies based on small molecule inhibitors (Supuran, 2008;Guler et al, 2010) or selective antibodies with inhibitory effects (Xu et al, 2010). It is noteworthy, however, that some studies on gastric and oesophageal tumours have shown a lack of positive correlation between CAIX expression and cancer progression (Pastorekova et al, 1997;Turner et al, 1997).…”
Section: Caix May Have An Important Role In Tissue Growth and Developmentioning
confidence: 92%
“…6A10 was the first and remains the best-described antibody for the inhibition of CA12 hydratase enzyme activity, with a potential biological role in the reduction of tumor growth 15,20,21 . However, only very few antibodies that can specifically bind and inhibit the hydratase activity of CA9 have appeared in the literature, such as the recently described MSC8 antibody 22,23 . Lack of effective and efficacious screening methods, which are easy to perform and offer a rapid and high throughput system for identifying CA9 and CA12 blocking antibodies, is believed to be one of the main reasons for this failure.…”
Section: Introductionmentioning
confidence: 99%